Target-Specific Delivery and Bioavailability of Pharmaceuticals via Janus and Dendrimer Particles - Jaison Jeevanandam; Kei Xian Tan; João Rodrigues; Michael K. Danquah (Pharmaceutics, 2023)
Nanosized Janus and dendrimer particles have emerged as promising nanocarriers for the target-specific delivery and improved bioavailability of pharmaceuticals. Janus particles, with two distinct regions exhibiting different physical and chemical properties, provide a unique platform for the simultaneous delivery of multiple drugs or tissue-specific targeting. Conversely, dendrimers are branched, nanoscale polymers with well-defined surface functionalities that can be designed for improved drug targeting and release. Both Janus particles and dendrimers have demonstrated their potential to improve the solubility and stability of poorly water-soluble drugs, increase the intracellular uptake of drugs, and reduce their toxicity by controlling the release rate. The surface functionalities of these nanocarriers can be tailored to specific targets, such as overexpressed receptors on cancer cells, leading to enhanced drug efficacy The design of these nanocarriers can be optimized by tuning the size, shape, and surface functionalities, among other parameters. The incorporation of Janus and dendrimer particles into composite materials to create hybrid systems for enhancing drug delivery, leveraging the unique properties and functionalities of both materials, can offer promising outcomes. Nanosized Janus and dendrimer particles hold great promise for the delivery and improved bioavailability of pharmaceuticals. Further research is required to optimize these nanocarriers and bring them to the clinical setting to treat various diseases. This article discusses various nanosized Janus and dendrimer particles for target-specific delivery and bioavailability of pharmaceuticals. In addition, the development of Janus-dendrimer hybrid nanoparticles to address some limitations of standalone nanosized Janus and dendrimer particles is discussed.